Strategi membaca teks bahasa Arab dalam kalangan pelajar Melayu / Nurul Huda Mohamad - Mohamad, Nurul Huda (2012)
The objective of this research are, firstly, to identify the most used and the least used reading streategies among Malay students. Secondly, the research aims to find out the different usage of reading strategies according to gender, and lastly, to identify the correlation between reading strategies and the students‟ achievement. The instrumental used in this research is Survey Of Reading Strategies (SORS). This survey contain 30 item with 5 Likert scale. The strategies is divided into 3 categories; Problem Solving Strategies, Support Strategies and Global Strategies. Beside that, Reading Proficiency in Arabic Test is also used to investigate the students‟ latest proficiency of Arabic Language, an observation has been held to support the main research findings. After some adjustment on the instrument, a pilot study had been done to ensure the reliability of the instrument. 50 respondent out of 80 people of the sample‟s population had been chosen to ensure the questionaire and the Arabic Language Proficiency Test. The obtain raw data is analysed using Statistic Package for Social Science (SPSS) version 12. The findings shows that 5 strategies that been used most came from Problem Solving Strategies and 4 strategies had been used the least are from Global Strategies. The t-test hold had shown no significant differences in Reading Strategies used by male and female students. While, the Pearson r correlation test shows no significant relation between the usage of texts reading strategies with the achievement.